College writing skills and college writing skills with readings - Langan, John (McGraw-Hill, 2005)
This edition, features Langan's renowned clear writing style and wide range of writing assignments and activities that reinforce the four essentials of good writing: Unity, Support, Coherence and Sentence Skills.